COMPREHENSIVE MIDWIFERY CARE TO MRS “S” G1P0A0 FEET SLUMP WITH HYDROTHERAPY AND PAIN AT ONE PERIOD OF LABOR WITH MASSAGE EFFLEURAGE AT “BI” CLINIC CIPATAT WEST BANDUNG DISTRICT - Hasanah, Uswatun; Fatonah HS, Sofa; Sarikah , Iik; Karwati , Karwati (jfpublisher, 2022)
Introduction. Leg swelling is an inconvenience that often occurs in the third trimester of pregnancy and can be treated with hydrotherapy to reduce discomfort to the mother. Pain associated with childbirth is one of the most intense forms of pain that a woman in labor experiences. So it requires care to reduce pain and discomfort in the labor process, the method for pain reduction is by massage effleurage. Findings at BI” Clinic from 50 pregnant women as many as 37 pregnant women (75%) experienced leg swelling discomfort. This study aims to determine the effect of the intensity of leg swelling after hydrotherapy on leg swelling in the third trimester, effleurage massage in the first stage of labor. Methods. The study method sed is a case study by conducting an assessment to provide care. The study subject Mrs.